Brush-Structured Chitosan/PolyHEMA with Thymine and Its Synergistic Effect on the Specific Interaction with ssDNA and Cellular Uptake - Phunpee, Sarunya (Langmuir : the ACS journal of surfaces and colloids, 2022)
Cationic polymers are known to attach on an anionic cell surface and favor gene transportation/transfection into the cells. However, when the positive charges accumulate, they tend to cause cell damage and delivery failure. Chitosan (CS) is a potential cationic bio-derived polymer whose chemical structures can be modified to fine-tune the charges as well as the add-on functions. The present work demonstrates (i) the decoration of a nucleic acid sequence-like brush structure on CS to allow the specific interaction with DNA and (ii) delivery into the cell. By simply applying mercaptoacetic acid as the chain transfer agent, the grafting of poly(hydroxyethyl methacrylate) (PHEMA) containing Thy (P(HEMA-Thy)) on CS is possible. The brush-like P(HEMA-Thy) leads Thy moieties to be in sequences. The Thy sequences perform as poly[T] for the specific interaction with ssDNA. The synergistic effect of CS and Thy sequences, i.e., electrostatic and base pairing interactions, results in an effective and efficient binding with ssDNA as well as significant delivery, especially in cellular uptake and cell viability. The use of CS in combination with Thy sequences in brush-like structures on CS is a model for other polysaccharides to be conjugated with the as-designed nucleic acid sequences for potential gene delivery